A case of abdominal-pelvic infiltrative lesion of chronic active Epstein–Barr virus infection. (August 2020) - Xue, Tianjiao; Ye, Huan; Li, Fang; Luo, Chengyu; Liu, Shumei; Luo, Jing; Tan, Yanguo
Epstein–Barr virus (EBV) belongs to a subfamily of herpesviruses, also known as human herpesvirus type 4. EBV is widely distributed in the population, with a high infection rate of 90%. EBV infects mainly B lymphocytes, stimulates cell proliferation and transformation and even causes cancer. In recent years, it has been found that it can also infect T lymphocytes, epithelial cells and natural killer (NK) cells and can cause related diseases. EBV infection can cause a variety of clinical symptoms and clinical manifestations, which brings some confusion to clinical diagnosis and easily leads to missed diagnosis and misdiagnosis. In this article, we report a case of EBV-induced severe abdominal and pelvic infection, which eventually led to death.